SoK: The Evolution of Trusted UI on Mobile - Bove, Davide (ASIA CCS '22: Proceedings of the 2022 ACM Asia Conference on Computer and Communications Security, 2022)
In mobile security research, one of the many challenges is the lack of trusted user interfaces (TUI). Currently, users are not able to reliably identify which screen content is genuine and which is potentially manipulated. The concepts of trusted displays and user interfaces, which offer a high confidence in the trustworthiness of screen contents, are not universally implemented on current consumer devices. In this paper, we systematically analyze the developments in the field of TUIs on mobile devices over seven years. We present a new taxonomy to define and categorize challenges and issues in current UI designs, with a focus on issues that negatively affect the security of the whole OS. In addition, we suggest directions where contributions in research could solve these issues.
Keywords: trusted ui; mobile security; android; trusted execution